Coherent Anti-Stokes Raman Scattering Microscopy: A Label-Free Method to Compare Spinal Cord Myelin in Different Species - Poulen, Gaëtan; Gerber, Yannick N; Perez, Jean-Christophe; Oubarrahou, Khadidja; Lonjon, Nicolas; Vachiery-Lahaye, Florence; Boukhaddaoui, Hassan; Perrin, Florence E. (Frontiers in Physics, 2021)
Many histological techniques are used to identify and characterize myelin in the mammalian nervous system. Due to the high content of lipids in myelin sheaths, coherent anti-stokes Raman scattering (CARS) microscopy is a label free method that allows to identify myelin within tissues. CARS excites the CH2 vibrational mode at 2845cm-1 and CH2 bonds are found in lipids. In this study we have used CARS for a new biological application in the field of spinal cord analysis. We have indeed compared several parameters of spinal cord myelin sheath in three different species i.e.; mouse, lemur and human using a label-free method. In all species, we analyzed the dorsal and the lateral funiculi of the adult thoracic spinal cord. We identified g-ratio differences between species. Indeed, in both funiculi, g-ratio was higher in mouse than in the two primate species and the myelin g-ratio in lemur was higher than in human. We also detected a difference in g-ratio between the dorsal and the lateral funiculi only in human. Furthermore, species differences between axon and fiber diameters as well as myelin thickness were observed. These data may reflect species-specificities of conduction velocity of myelin fibers. Comparison of data obtained by CARS imaging and fluoromyelin staining, a method that similarly to CARS does not require resins embedding and dehydration, displays similar results. CARS is therefore a free label alternative to other microscopy techniques to characterize myelin in healthy and neurological disorders affecting the spinal cord.